A Sequential Isolation and Isolate Identification of Thermophilic Oil Degrading Bacteria from Bangko Reservoir - Megga Ratnasari Pikoli; Pingkan Aditiawati; Dea Indriani Astuti (Institute for Research and Community Services (LPPM) ITB, 2000)
Sari. Telah dilakukan isolari bakteri termofilik pendegradasi minyak bumi dari Sumur Bangko dengan cara bertahap karena prosedur isolasi biasanya belum tentu dapat mengisolasi bakteri pendegradasi secara lengkap. Isolasi tahap I dilakukan langsung dari crude oil di dalam medium basal Stone Mineral Salt Solution ditambah ekstrak ragi (SMSSe) pada 50 °C. Isolasi tahap II dan III dilakukan dari sumber isolat yang sama, medium basal dan kondisi kultur yang sama, tetapi medium pengisolasi diperkaya dengan minyak sisa degradasi (MSD) isolat campuran tahap sebelumnya. Pada tahap I diperoleh 4 isolat, yaitu Bacillus polynyxa, B. licheniformis, Bacilus sp.1, dan Pseudomonas aeruginosa; pada tahap II diperoleh 3 isolat, yaitu Bacillus sp.2, B. stearothermophllus, dan B. brevis; sedangkan pada tahap III hanya diperoleh 1 isolat, yaitu B. coagulans. Semua isolat ini nantinya digunakan untuk mendegradasi crude oil. A Sequential Isolation and Isolate Identification of Thermophilic Oil Degrading Bacteria from Bangko ReservoirAbstract. A study on the isolation of thermophilic oil-degrading bacteria from the crude oil (petroleum) of Banko reservoir has been conducted on a sequential way. The conventional isolation procedure did not isolate the bacteria completely. The first isolation stage was performed directly on the crude oil sample by using Stone Mineral Salt Solution plus yeast extract (SMSSe), as basal medium, at 50°C. The second and third isolation stages used the same source, basal medium, and condition as the first stage, but were enriched with a depleted-oil obtained from the crude oil degraded from the previous stage's mixed culture bacteria. Four bacterial isolates were recovered from the first isolation stage, identified as Bacillus polymyxa, B. Licheniformis, Bacillus sp.1, and Pseudomonas aeruginosa. The second stage gave another three different bacterial isolates, identified as Bacillus sp.2, B. stearothermophillus, and B. brevis; whereas the third stage gave only one isolate namely Bacillus coagulans. These isolates could be applied for the degradation of crude oil.